Geodynamic Modeling of Edge-Delamination Driven by Subduction-Transform Edge Propagator Faults: The Westernmost Mediterranean Margin (Central Betic Orogen) Case Study - Negredo, A. M.; Mancilla, F. d. L.; Clemente, C.; Morales, J.; Fullea, J. (Frontiers in Earth Science, 2020)
Mantle tearing at slab edges is common in scenarios where retreating slabs face continental margins. Such tearing is often accommodated via subvertical STEP (Subduction-Transform Edge Propagator) faults that cut across the entire lithosphere resulting in sharp lateral thermal and rheological variations across the juxtaposed lithospheres. This setting favours the occurrence of continental delamination, i.e. the detachment between the crust and the lithospheric mantle. In this study we investigate by means of thermo-mechanical modelling the conditions for, and consequences of, delamination associated with STEP faults without imposing any ad hoc forcing. We find that conditions favoring continental delamination are: i) a strong density contrast between the orogenic and the back-arc lithospheres; ii) a significantly thinned back-arc lithosphere; and iii) a relatively thick and weak lower crust in the continental margin. Our model analysis indicates that delamination is very sensitive to the initial thermal and rheological conditions, transitioning from a stable to a very unstable and rapidly evolving regime. We find two clearly differentiated regimes attending at the time at which the process becomes unstable: fast and slow delamination. Although the final state reached in both the fast and slow regimes is similar, the dynamic surface topography evolution is dramatically different. As a inspiring study case for benchmarking purposes we have chosen a well-studied example recently imaged with unprecedented seismic resolution: the STEP fault under the central Betic orogen, at the northern edge of the Gibraltar arc subduction system (westernmost Mediterranean Sea). The Gibraltar arc subduction is the result of the fast westward roll-back of the Alboran slab and it is in its last evolutionary stage, where the oceanic lithosphere has been fully consumed and the continental lithosphere attached to it collides with the overriding plate.